IS BITCOIN AN OPPORTUNITY OR A THREAT TO THE RELEVANCE OF ACCOUNTING INFORMATION? - Marçal, Ronan Reis; Chacon, Bruno Prata; Flach, Leonardo (Revista Mineira de Contabilidade, 2020)
Positive accounting research is the one that addresses the informational perspective of accounting (Watts & Zimmerman, 1990). In this scenario, studies on the relevance of accounting information in the capital market stands out. Some of these surveys consider the effects of firms’ extrinsic variables on the ability of accounting information to predict stock prices. Considering the apparent inverse relationship between Bitcoin and the capital markets, being this cryptocurrency able to be used as hedge for investors in these markets (Bouri et al., 2017), the purpose of this study was to analyze the influence of the Bitcoin price in the market value of the companies listed on the [B]³ in conjunction with the accounting information. Panel data regressions were performed considering the stock price and return as dependent variables and Net Income, Equity and Bitcoin quotation as regressors. From 356 observations concerning 89 different companies, it was possible to verify, with a 95% confidence level, that the companies’ market value is negatively influenced by Bitcoin’s price increase. This suggests a preference for investments in the cryptocurrency market over the capital market when the first one is on the rise, corroborating Bouri et al. (2017). In addition, Equity loses significance and Net Income is reduced when Bitcoin is included in the model, indicating a potential risk to accounting information in terms of relevance. The research has limitations regarding the use of a single cryptocurrency in the face of several existing ones and also in the selection of only one exercise as sample cut.